Taking new Perspectives on Value Creation: - Noll, Sebastian (2016)

(untitled)
Previous research has only provided evidence that companies held by private equity and venture capital firms that to have quicker, more efficient and more engaging decision making processes than non-private equity and venture capital backed companies. However, no reference has been made to the way how these decision making processes are achieved and how private equity and venture capital firm intervene in this context. Moreover, previous research has ignored the questions how certain decisions are explained in how portfolio companies ensure clarity in regard to new expectations and responsibilities that emerge from certain decisions. This is particularly important in private equity and venture capital decisions which are driven by decisions that result in significant changes within the portfolio companies. The key objective of this work is to argue for an extension of the three previously known types of value creation activities of private equity firms which include financial engineering, governance engineering and operational engineering by adding decision engineering as the fourth type of value creation activities. The concept of decision engineering was based on the principles of fair process defined by Kim and Mauborgne (2003) which consist of engaging, explanation and expectation clarity. In order to provide a basis for this argument and to close the existing research gap, this work aims to answer the following two research questions: “How do private equity and venture capital firms shape decision making processes within their portfolio companies?” and “To which degree are these decision making processes consistent with the principles of fair process?”. In order to answer these research questions, a collective case study approach was applied and qualitative data were gathered through semi-structured interviews which were conducted with seven participants, including five top and middle managers from companies held by private equity firms, one portfolio manager of a private equity firm and a CEO of a venture capital firm. All participants were askes a set of predetermined questions which were based on the principles of fair process. If necessary, some emerging questions were asked as well in order to adapt to the course of the interview. The analysis of the data was conducted by applying a theory-driven approach to content analysis and has led to the following key findings: first, decision making processes can be made quicker, more efficient and more engaging by simplifying organisational structures and assigning new responsibilities. Second, employees play an important role in the decision making process and can generate valuable ideas that can even shape the long-term strategy on an organisation since they are often closer to the subject of decision than managers are. Third, providing all individuals that are affected by a certain decision sufficient explanation in regard to the decision making process is absolutely necessary. If decisions are not explained sufficiently, even decisions that lead to positive outcomes can cause negative reactions. On the other hand, negative reactions can be significantly reduced when decision making processes are made transparent, even in regard to decisions that lead to negative outcomes. A high level of transparency can often help to find solutions in decisions that impact individuals negatively. Fourth, clarifying targets set by the private equity or venture capital firm receives a high level of attention. However, processes that are associated with these targets need to receive sufficient attention as well. Based on the interview data, it seems like changes in evaluation criteria or responsibilities are not always clear. Finally, investors and portfolio companies need to make sure that all principles of fair process are practised. In most of the cases, the principles of fair process were only practiced partially.